Development of student worksheets based on socio-scientific issues: Its influence on chemical literacy and students’ scientific attitudes - Ulliva, Syafira Rachmatyah; Prodjosantoso, A.K. (Indonesian Journal of Educational Development (IJED), 2025)
Based on the needs analysis, it is indicated that students’ chemical literacy and scientific attitudes at SMA Negeri 1 Bayung Lencir remain low. The cause was the limited availability of chemistry learning resources that are contextualized to real life. Therefore, this study aimed to know the characteristics, feasibility, and practicality of developing student worksheet products based on Socio-Scientific Issues (SSI) on the chemical bond topic and its influence on students’ chemical literacy and scientific attitudes. The type of this study is Research and Development (R&D) with the 4D development model by Thiagarajan. In the Define stage, a needs analysis was conducted; in the Design stage, the initial design of the worksheets was created; in the Develop stage, SSI-based student worksheets were produced after undergoing validation; and in the Disseminate stage, the SSI-based student worksheets were distributed to a class of X students at SMA Negeri 1 Bayung Lencir. The results showed that the student worksheet was produced in printed form, was feasible for use, practical, and there was a significant difference in students’ chemical literacy. However, no significant difference was observed in students’ scientific attitudes. Further research is recommended to develop SSI-based worksheets for other abstract chemistry topics and to explore their influence on students' scientific attitude.